2014
DOI: 10.1055/s-0034-1395597
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Docetaxel in Osteosarcoma by the Inhibition of Wnt Signal Channel

Abstract: Osteosarcoma (OS) is the most common type of malignant bone tumor in adults and children. Despite the great strides in biology and medicine, the survival rate of patients with metastatic disease remains very poor. This rate has been staggering with recurrence and metastasis. In the present study, we proposed Wnt/β-catenin pathway as a key biological target for the effective treatment in OS. Wnt signaling has been reported to play important roles in osteoblastogenesis. We hypothesized that docetaxel (DTX) will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Certain scholars have reported that TXT can inhibit the proliferation of OS cells and induce apoptosis, and that such inhibition is time-and dose-dependent (48,49). Combination therapy using TXT and gemcitabine (GEM) has also been reported to enhance antitumor effects (50,51).…”
Section: Second-line Treatment Of Osmentioning
confidence: 99%
“…Certain scholars have reported that TXT can inhibit the proliferation of OS cells and induce apoptosis, and that such inhibition is time-and dose-dependent (48,49). Combination therapy using TXT and gemcitabine (GEM) has also been reported to enhance antitumor effects (50,51).…”
Section: Second-line Treatment Of Osmentioning
confidence: 99%
“…After each incubation time, the media were replaced with 2 mg/ml of MTT (Sigma) solution and incubated for 4 h in a cell culture incubator. The intracellular formed formazan crystals were solubilized using DMSO and the Absorbance measurements were performed at 570 nm by a plate reader [17,18]. The viability of ASCs in each treatments groups were calculated and reported in results.…”
Section: Colorimetric Viability Assaymentioning
confidence: 99%
“…Aberrant signaling by Wnt can also result in increased cell proliferation and migration through both the canonical b-catenin and noncanonical pathways [34][35] . Accordingly, many research efforts have shown promise for OS therapy through inhibition of Wnt and downstream proto-oncogenes [36][37][38] . However, similar to Runx2, it appears that normal Wnt signaling is also finely tuned, with other studies demonstrating a correlation between decreased pathway activity and hypoxic chemoresistance in OS [39] .…”
Section: Molecular Basis Of Os and Potential Targets For Therapymentioning
confidence: 99%